Towards the neural basis of magnetoreception: a neuroanatomical approach - Nemec, Pavel; Burda, Hynek; Oelschläger, Helmut H A (Die Naturwissenschaften, 2005)
After more than two decades of intensive research, the physiological mechanisms of animal magnetoreception remain enigmatic. The primary magnetoreceptors are still unknown and our knowledge of the neural substrate subserving magnetic orientation is meagre. Here we argue that this dismal outcome can be largely attributed to the fact that the potential of recently available neurobiological techniques has not been utilized, review some of these techniques and propose a step by step scenario for future research, concentrating on the heuristic potential of instrumentalizing inducible transcription factors (ITFs) such as Jun, Fos, Fos-related antigens and Krox. ITFs can be used as markers of neuronal activation in experiments on freely moving animals performing magnetically based orientation tasks, in experiments on anaesthetised or restrained animals stimulated magnetically, and in experiments employing treatments that specifically disrupt magnetoreception. Therefore they can serve as tools for identifying neurons involved in the detection and processing of magnetic information. When used in combination with other neurobiological tools, ITFs can also be useful for a more comprehensive description of the involved neural networks, for the identification of magnetoreceptors and, in the case of the photoreceptor-based mechanism, also for studying the involvement of specific light-sensitive molecules in the primary transduction process of magnetoreception. Limitations and pitfalls of the proposed approach are also discussed.
Keywords: Genes, fos; geny fos; nervový systém - fyziologické jevy; elektromagnetická pole; Nervous System Physiological Phenomena; Electromagnetic Fields; magnetismus; Animals; Gene Expression Regulation; nervový systém; zvířata; Magnetics; neurony; regulace genové exprese; Nervous System; Neurons